Development of diagnostic competencies of educational psychologist in professional training - Aralbaeva, Ryszhamal; Naubaeva, Khapiza; Abishev, Nurlan; Taszhurekova, Zhumagul; Zhexembayeva, Zhadra (Institute of Advanced Engineering and Science, 2024)
In the era of globalization, enhancing the development of diagnostic competencies among educational psychologists in Kazakhstan is a crucial aspect of improving higher education quality. The purpose of the study is to substantiate and implement the methodology for the development of diagnostic competencies of future educational psychologists in higher educational institutions of Kazakhstan as a guarantee of their readiness to carry out professional activities. The methodological approach involves developing methods for fostering diagnostic competencies, employing empirical techniques such as comparison, systematization, classification, and generalization of theoretical data, conducting surveys, testing, and modeling training methods for future educational psychologists. An experimental study conducted on the premises of Zhetysu University named after I. Zhansugurov has developed methodological tools to increase the readiness of future educational psychologists for the development of diagnostic competencies in professional training, namely: the implementation of readiness components with selected methods for their formation. After conducting an experimental study, promising areas for improving the methodology of readiness of future educational psychologists for the development of diagnostic competencies in Kazakhstan were established.